State of the Climate in Africa 2024 - World Meteorological Organization (World Meteorological Organization (WMO), 2025)
The State of the Climate in Africa report reflects the urgent and escalating realities of climate change across the continent. It also reveals a stark pattern of extreme weather events, with some countries grappling with unprecedented flooding caused by excessive rainfall and others enduring persistent droughts and water scarcity. WMO and its partners are committed to working with WMO Members to build resilience and strengthen adaptation efforts in Africa to protect lives and economies through initiatives such as Early Warnings for All. It is my hope that this report will provide inspiration and guidance for collective action to address increasingly complex challenges and cascading impacts.